Fast human body measurement based on a single kinect - Dao, Nguyen Luc (2014)
Human body measurements are important information in many industries such as clothing, entertainment and healthcare. The development of commodity depth camera, especially Microsoft Kinect has paved a new way for human body measurement. The existing Kinect based body measurement methods are too time-consuming since their purposes also include 3D reconstruction. In this report, we present a Kinect-based simple but fast and effective solution that is tailored only for human body measurement. In particular, our method captures four views of a subject’s body and constructs a 3D point cloud for each view. The point clouds are then registered and merged to have a full body cloud. Three cloud based measurement methods are proposed including interactive circular measurement, interactive straight measurement and automatic circular measurement. To conduct the experiments, we implemented an application following our proposed method. The experimental results show that our method requires much shorter execution time than the previous works while still producing measurements with comparable quality.